2019
DOI: 10.3389/ffgc.2019.00007
|View full text |Cite
|
Sign up to set email alerts
|

Water Table Drawdown Alters Soil and Microbial Carbon Pool Size and Isotope Composition in Coastal Freshwater Forested Wetlands

Abstract: Loss of coastal wetlands is occurring at an increasingly rapid rate due to drainage of these wetlands for alternative land-uses, which also threatens carbon (C) storage in these C-rich ecosystems. Wetland drainage results in water table drawdown and increased peat aeration, which enhances decomposition of previously stabilized peat and changes stable C isotope profiles. The effect of water table drawdown on the pool size and δ 13 C signature of plant C, soil organic C (SOC), and microbial biomass C (MBC) acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 89 publications
2
8
0
Order By: Relevance
“…The response of microbes to drainage is likely to depend on peatland type, the alteration of water table fluction, and the extent of spatiotemporal variation (Andersen, Chapman, & Artz, 2013;Krista Jaatinen et al, 2008;Minick et al, 2019;Peltoniemi, Fritze, & Laiho, 2009). Our study found that both water table and drainage age significantly affected the microbial community structure and compositions ( Figure 2), which was consistent with many studies (Jaatinen et al, 2007;Urbanova & Barta, 2016).…”
Section: Microbial Characteristics Varied In Relation Toduration Ofdrsupporting
confidence: 89%
See 1 more Smart Citation
“…The response of microbes to drainage is likely to depend on peatland type, the alteration of water table fluction, and the extent of spatiotemporal variation (Andersen, Chapman, & Artz, 2013;Krista Jaatinen et al, 2008;Minick et al, 2019;Peltoniemi, Fritze, & Laiho, 2009). Our study found that both water table and drainage age significantly affected the microbial community structure and compositions ( Figure 2), which was consistent with many studies (Jaatinen et al, 2007;Urbanova & Barta, 2016).…”
Section: Microbial Characteristics Varied In Relation Toduration Ofdrsupporting
confidence: 89%
“…It was found that microorganisms are very sensitive to the availability of water and oxygen in wetland ecosystems (Jaatinen, Fritze, Laine, & Laiho, 2007). Water table drawdown enhances the activities of extracellular enzyme (Wiedermann, Kane, Potvin, & Lilleskov, 2017), increases microbial biomass (Minick, Mitra, Li, Noormets, & King, 2019), and thus changes the GHG emissions resulting from microbial activities (Wang et al, 2017;Zhong et al, 2017). As well the vulnerability or resilience of microbial communities to water table drawdown is likely to depend on duration of drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increases in the diversity of biogeochemical processes occurring at the individual hummock or hollow scale (Deng et al, 2014) likely aggregate to influence ecosystem functioning at large scales. For example, microtopographic niche expansion allows for local material and solute exchange between hummocks and hollows, creating coupled aerobic-anaerobic conditions with emergent outcomes for denitrification (Frei et al, 2012) and carbon emission (Bubier et al, 1995;Minick et al, 2019a, b).…”
Section: Broader Implicationsmentioning
confidence: 99%
“…Negative feedbacks eventually limit this growth; otherwise, hummocks would have no vertical or lateral limit. Vertical negative feedbacks may result from increased decomposition as hummocks grow vertically and their soils become more aerobic (Minick et al, 2019a, b; bottom, dashed loop on the right-hand side of Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Saltwater intrusion, a direct result of SLR, into freshwater wetlands alters soil C cycling processes (Ardón et al, 2016(Ardón et al, , 2018, particularly that of methanogenesis (Baldwin et al, 2006;Chambers et al, 2011;Dang et al, 2019;Marton et al, 2012) and microbial activity (e.g., extracellular enzyme activity, Morrissey et al, 2014;Neubauer et al, 2013). Saltwater contains high concentrations of ions, notably sulfate (SO 2− 4 ), which support high rates of SO 2− 4 reduction compared to freshwater wetlands (Weston et al, 2011).…”
Section: Introductionmentioning
confidence: 99%